Ozone therapy for musculoskeletal disorders Current concepts - Akkawi, Ibrahim (Acta Biomedica Atenei Parmensis, 2020)
Medical O3 therapy combines a mixture of oxygen (O2)-O3 and prepared through conversion of pure O2 into O3 using special medical generators. O3 has multiple mechanisms of action: antalgic, antiinflammatory, and antioxidant effects. These therapeutic effects are obtained by amelioration of tissue oxygenation, accelerating glucose usage in cellular metabolism, improving protein metabolism, increasing erythrocyte activity, inhibiting inflammatory mediators, reducing the synthesis of prostaglandins and decreasing joint oxidative stress. O2-O3 has been proved to be effective in reducing pain in many musculoskeletal disorders including low back pain, lumbar disk herniation, cervical pain, cervical disk herniation, failed back surgery syndrome, degenerative spinal disease, knee osteoarthritis, meniscal injuries, sacroiliitis, plantar fasciitis and carpal tunnel syndrome, with rare adverse effects if judiciously used according to precisely defined guidelines.